Oxidation of H2S in acid solution by Thiobacillus ferrooxidans and Thiobacillus thiooxidans - Oprime, MEAG; Garcia, O.; Cardoso, Arnaldo Alves [UNESP] (Elsevier B.V., 2001)
Qualitative and quantitative oxidation tests of H2S in acid solution were carried out using Thiobacillus ferrooxidans and Thiobacillus thiooxidans species, Experiments were performed using solutions of H2SO4 (pH 2.0) containing H2S in initial concentrations ranging from 5 to 100 ppm. in shake flasks at 150 rpm and 30(circle)C. In these solution, this gas was not very stable and was quickly liberated. However, at low concentration (less than 5 ppm) it becomes stable and could only be removed from solution by oxidation. The results obtained indicated that the presence of either T. ferrooxidans or T. thiooxidans causes a significant reduction in H,S concentration (more than 99%) in relation to the sterile control, No differences in oxidation efficiency between these two species were detected. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: H2S oxidation; Thiobacillus thiooxidans; Thiobacillus ferrooxidans